1999
DOI: 10.1021/jp984176n
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Band of the Photographic Compound AgCl

Abstract: Electronic structure calculations on the photographic compound AgCl are reported. It is shown that the conduction band has a large Cl-4s character, contrary to the common picture of the conduction band being derived from Ag-5s states. Possible consequences for the photographic process are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 18 publications
9
34
0
Order By: Relevance
“…The LCAO-based energy bands and DOS have been plotted using DL Visualize software [37]. Except for some fine structures and bandgaps, the overall Original Paper shape of our energy bands is in agreement with the reported data [7][8][9][11][12][13]. Here, we interpret the energy bands (with energy scale as E -E F ) deduced from the FP-LAPW approach in the energy range -6.0 eV to 12.0 eV as shown in Fig.…”
Section: Lcao Calculationssupporting
confidence: 84%
See 1 more Smart Citation
“…The LCAO-based energy bands and DOS have been plotted using DL Visualize software [37]. Except for some fine structures and bandgaps, the overall Original Paper shape of our energy bands is in agreement with the reported data [7][8][9][11][12][13]. Here, we interpret the energy bands (with energy scale as E -E F ) deduced from the FP-LAPW approach in the energy range -6.0 eV to 12.0 eV as shown in Fig.…”
Section: Lcao Calculationssupporting
confidence: 84%
“…Using ab-initio HF pseudopotential linear combination of atomic orbitals (LCAO), Apra et al [6] have reported the electronic structure of AgCl. Regarding computation of electronic structure using full-potential augmented planewave (FP-LAPW) method, Boer and de Groot [7] have used WIEN95 code incorporating the local density approximation (LDA). Okoye [8] has used FP-LAPW with the generalized gradient approximation (GGA) of PerdewBurke-Ernzerhof (PBE) to investigate the pressure dependence of bandgaps in silver halides.…”
mentioning
confidence: 99%
“…III D, which describe the ''core'' region of the asymptotically flat solitons, we can use the powerful AdS/CFT correspondence machinery to identify the corresponding states in the CFT. The dual CFT for the asymptoticallyAdS 3 S 3 T 4 spaces with radius ' Q 1 Q 5 1=4 is a sigma model with target space a deformation of the orbifold T 4 N =S N [41][42][43], where…”
Section: Relation To Cftmentioning
confidence: 99%
“…These operators are expected to be dual to multi-particle states in the dual string theory. In the case of AdS 3 × S 3 × M 4 it was found in [12] that multiparticle states in supergravity were needed to account for the elliptic genus computed from the dual CFT.…”
Section: Multiple Brane Statesmentioning
confidence: 99%